# Factoring (Objective 1.

3) is the process of finding two or more expressions whos e product is equal to a given expression, that is, is to transform this polynomi al as the product of two or more factors. Case 1. Factoring by common factor (if monomial): write the common factor (CF) as a coefficient of a parenthesis and p laced in the same ratios that are the result of dividing each term of the polyno mial by FC Examples: a) Resolve (or factor) in terms of a 2 + 2 ª. The common fa ctor (CF) in the two terms is therefore stands in front of the parentheses (). W ithin the parentheses are located a result of: February 2 a2 2a + = + = a + 2, t herefore: a (a +2). Thus: a 2 + 2a = a (a + 2) FC FC aab) Explode (or factor) 10 b - 30ab. The coefficients 10 and 30 have common factors 2, 5 and 10. We took th e 10 because he always takes the greatest common factor. The common factor (CF) is 10b. Therefore: 10b - 10b 30ab 2 = (1 - 3ab) c) Decompose: 18mxy 2 - 2y 2 + 2 x 54m 36 m 2 = 18my 2 (x - 3mx 2 + 2) d) and 3 Factoring 6x - 2y 9NX 12nx 3 + 3y 3 - 2x 4y 3n 3 = 3x and 3 (2 - 4NX 3NX + 2 - n 2x 3) Case 2. Factoring by commo n factor (polynomial case) a) Decompose x (a + b) + m (a + b) These two terms ha ve a common factor the binomial (a + b), so you put (a + b) as coefficient of a break in which we write the quotients of dividing the two terms of the expressio n given by the common factor (a + b), ie: x a b a b m x m and ha s : a b a b x (a + b) + m (a + b) = (a + b) (x + m) b) Decompose 2x (a - 1) - and (a - 1) The common factor is (a - 1), thus dividin g the two terms of the expression given by the common factor (a - 1), with we ha ve: 2 x a 1 and a 1 2x and then: a 1 1 a 2x (a 1) - and (a - 1) = (a - 1) (2x - y) c) Decompose f (x + 2) + x + 2 can write this expression as follows: m (x + 2) + (x + 2) = m (x + 2) + 1 (x + 2) The common factor (x + 2) so: f (x + 2) + 1 (x + 2) = (x + 2) (m + 1) d) Decompose a (x + 1) - x - 1 When entering the last two terms in parentheses p receded by the sign (-), we have: a (x + 1) - x - 1 = a (x + 1) - (x + 1) = a (x + 1) - 1 (x + 1) = (x + 1) (a - 1) e) Factoring 2x (x + y + z) - x - y - z. With this: 2x (x + y + z) - x - y - z = 2x (x + y + z) - (x + y + z) = (x + y + z) (2x - 1) f) Factoring (x - a) (y + 2) + b (y + 2). The common factor is (y + 2), and divi ding the two terms of the expression given by (y + 2) we have: x A and x and b , Then: (X - a) (y + 2) + b (y + 2) = (y + 2) (x - a + b) g) Resolve (x + 2) (x - 1) + (x - 1) (x - 3). Dividing by the common factor (x 1): 2 1) and x 1 x 3 x 3, therefore: x 1 x 1 x x 2 x 1 b 2 2 and to and 2 2 and

(X + 2) (x - 1) - (x - 1) (x - 3) = (x - 1) (x + 2) - (x - 3) = (x - 1) (x + 2 -

x + 3) = (x - a) (5) = (x h) Factoring x (a - 1) + y (a - 1) - a + 1. x (a - 1) + y (a - 1) - a + 1 = x (a - 1) + y (a - 1) - (a - 1) = (a - 1) (x + y - 1) Case 3. Factoring by common factor (if grouping of terms): a) Decompose ax + bx + ay + by the first two terms have the common factor x and the last two common f actor. We group the first two in a parenthesis and the last two in another prece ded by the sign + for the third term has the sign (+): ax + bx + ay + by = (ax + bx) + (ay + by) = x ( a + b) + y (a + b) = (a + b) (x + y) There are several wa ys to make the group, provided that the two terms have some common factor groupe d and provided that the quantities are in parentheses after removing the common factor in each group, are exactly alike. If this is not possible, the given expr ession can not be broken by this method. In the above example we can group on 1. and 3rd. terms with the common factor and 2nd. and 4th. the common factor b, y: ax + bx + ay + by = (ax + ay) + (bx + by) = a (x + y) + b (x + y) = (X + y) (a + b) This result is identical to the previous one, since the order of the factors is immaterial. b) Factoring 3m 2 - 4m + 6mn - 8n. The first two terms have the common factor 3m and the other two common factor 4. Grouping: 3m 2 - 4m + 6mn - 8n = (3m 2 - 6mn ) + (4m - 8m) = 3m (m - 2n) + 4 (m - 2n) = (m - 2n) (3m + 4) c) Resolve 2x 2 - 3x - 4x + 6y. The first two terms have the common factor x and the last two common factor 2, then group them but introducing the last two term s in parentheses preceded by the sign - (because the sign of the 3rd. Term is -) for which should be changed the signand we have: 2x 2 - 3x - 4x + 6y = (2x 2 - 3x) - (4x - 6y) = x (2x - 3y) - 2 (2x - 3y) (x - 2) Another alternative is to bring 1o. and 3. terms with r 2x, and the 2nd. and 4th. 3y with common factor, thus we have: 2x + 6y = (2x 2 - 4x) - (3x - 6y) = 2x (x - 2) - 3y (x - 2) = ( x - 2) - 3y) = (2x common facto 2 - 3x - 4x (2x - 3y)

d) Decompose x + z 2 - 2ax - 2az 2 x + z 2 - 2ax - 2az 2 = (x + z 2) - (2ax + 2a z 2) = (x + z 2) - 2a (x + 2az 2) = (x + z 2) (1 - 2a) By grouping the terms 1o. and 3., 2nd. and 4th.: x + z 2 - 2ax - 2az 2 = (x - 2a x) + (z 2 - 2az 2) = x (1 - 2a) + z 2 (1 - 2a) = (1 - 2a) (x + z 2) e) Factoring 3ax - 3x + 4y - 4ay. 3ax - 3x + 4y - 4ay = (3ax - 3x) + (4y - 4ay) = 3x (a - 1) + 4y (1 - a) = 3x (a - 1) - 4y (a - 1) = ( a - 1) (3x - 4y) In the second line of example above, the pairs (a - 1) and (1 - a) have differen t signs, to make the same changes to the binomial (1 - a) making (a - 1), but fo r the product 4y (1 - a) does not change the sign will change the sign to the ot her factor making 4y - 4y. Thus, we change the signs to an even number of factor s, the sign of the product remains unchanged. In the example above, by grouping the terms 1o. and 4th., 2nd. and 3.: 3ax - 3x + 4y - 4ay = (3ax - 4ay) + (3x - 4 y) = a (3x - 4y) - (3x - 4y) = (3x - 4y) (a - 1) f) Factoring: ax - ay + az + x - y + z. ax - ay + az + x - y + z = (ax - ay + az ) + (x - y + z) = a (x - y + z) + (x - y + z) = (x - y + z) + (a + 1) Case 4. Factoring a perfect square trinomial: The rule for factoring a perfect s quare trinomial said that the square root is extracted in the first and third te rms of the trinomial and these roots are separated by the sign of the second ter m. The pair thus formed, which is the square root of the triad, is multiplied by itself or is squared. Examples a) Factoring m 2 + 2m + 1 m 1 m2 1 therefore : m 2 + 2m + 1 = (m + 1) (m + 1) = (m + 1) 2

b) Decompose 4x 2 + 25y 2 - 20x y. When ordering the trinomial: 4 x2 2 d 2 x 5, and 4x 2 - 20x and 25y + 2 = (2x - 5y) (2x - 5y) = (2x - 5y) 2

25 an

Importantly, either could be given as minuend roots, so in the above example we have: 4x 2 - 20x and 25y + 2 = (5y - 2x) (5y - 2x) = (5y - 2x) 2 because the dev elopment of this binomial is: (5y - 2x) 2 = 25y signs. 2 - 20x + 4x and 2 which is a identical expression 4x 2 - 20x + 25y and 2, as it has the same quantities with the same c) Decompose 1 - 16AX 2 + 2x 4 64th x 4 64th February 8AX re: 1 - 16AX 64th 2x 2 + 4 = (1 - 8AX 2) 2 = (8AX 2-1) 2 d) Factoring x 2 bx b2 4 April 2 b2 b This is a perfect square trinomial because the double product of the square root of x2 x by the square root of reproduces the second term. Then: x 2 b2 b 2 e) Factoring square root 1 b b2 is a perfect square because the square root 439 September 3 b2 b 11 and 42 then: conduncen the second term through 1BB 2, 233 4 3 9 March 2 March 2 bx x 2 4 1 2 and 1, therefo

1 1 bb 2 b 1 b 2 2

f) Resolve a 2 + 2a (a - b) + (a - b) 2 Rule to factor can be applied to cases w here the first or third term of the trinomial or both are compound expressions. In this case we have: 2 + 2a (a - b) + (a - b) 2 = [a + (a - b)] 2 = (a + a - b) 2 = (2a - b) 2 Page 8 of 13 Case 5. Factoring a trinomial of the form x 2 bx c factors are broken down into two pairs whose first term is x, ie the square root of the first term of t he trinomial. In the first factor, x is written after the sign of the second t erm of the trinomial, and the second factor, x is written after the multiplicati on sign is the sign of the second term by the sign of the third term. If the t wo factors among couples have equal signs, look for two numbers whose sum is the absolute value of the second term of the trinomial and whose product is the abs olute value of the third term of the trinomial, ourselves to be the second terms of the binomials. If the two factors among couples have different signs, look for two numbers whose difference is the absolute value of the second term of th e trinomial and whose product is the absolute value of the third term of the tri nomial. The largest of these numbers is the second term of the first pairing, an d the smaller the second term binomial. Examples: a) Factoring x 2 + 5x + 6 This triad is composed of two couples whose first term is the square root of x 2, or x: x 2 + 5x + 6 = (x) (x) In the first pairing, then x, becomes the sign (+) because the second term of th e trinomial (+) has 5x sign (+). In the second pairing, after x,write the multi plication sign is (+ 5x) by (+ 6), and as (+) for (+) da (+), then: x 2 + 5x + 6 (x +) (x +) Since in these pairs is equal signs, look for two numbers whose sum is 5 and whose product is 6. These numbers are 2 and 3, then: x 2 + 5x + 6 = (x + 2) (x + 3) Page 9 of 13 b) Factoring x 2 - 7x + 12 we have: x 2 - 7x + 12 (x) (x -) In the first pairing sets (-) by the sign of (- 7x). The second set (-) because multiplying (- 7x) by (+ 12) we have (-) by (+) da (-). As in the binomial is eq ual signs, look for two numbers whose sum is 7 and whose product is 12. These nu mbers are 3 and 4, then: x 2 - 7x + 12 = (x - 3) (x - 4) c) Factoring x 2 + 2x - 15 You have: x 2 + 2x - 15 (x +) (x -) In the first pairing puts the sign + 2x + The second set - because multiplying ( + 2x) by (- 15) we have (+) by (-) da (-). As the couples have different signs, we seek two numbers whose difference is 2 and whose product is 15. These numbers are 5 and 3. 5, which is the largest, is written in the first binomial: x 2 + 2 x - 15 (x + 5) (x - 3) d) Factoring x 2 - 5x - 14 Thus: x 2 - 5x - 14 In the first pairing is put - by the sign of - 5x In the second placed (+) because multiplying - by 5x - 14 we ha ve (- ) by (-) da (+) (x -) (x +) Page 10 of 13 As the couples have different signs, look for two numbers whose difference is 5 and whose product is 14. These numbers are 7 and 2. The seven, which is the larg est, is written in the first binomial: x 2 - 5x - 14 = (x - 7) (x + 2) e) Factor in a 2 - 13a + 40, a 2 - 13a + 40 = (a - 5) (a - 8)

f) Factoring x 2 - 6x - 216; x 2 + 6x - 216 (x +) (x -) We need two numbers whose difference is 6 and the product 216, which are not eas ily seen. To find them, is decomposed into its prime factors, the third term: 216 108 54 27 9 3 1 February 2 February 3 March 3 With these two products we are prime factors. By trial and error, varying the fa ctors of each product we obtain the two numbers that look like this: 2 × 2 × 2 = 8 2 × 2 × 2 × 3 = 24 2 × 2 × 3 = 27 to 8 December = 19, do not work 24-9 = 15, not to serve 18 to 12 = 6, do serve 3 × 3 × 3 = 27 3 × 2 × 3 = 9 3 × 3 = 18 Page 11 of 13 The numbers that we are 18 and 12, because their difference is 6 and its product necessarily 216, as we use these numbers for all the factors obtained in the de composition of 216, therefore: x 2 + 6x - 216 = (x + 18) (x - 12) 7) Factoring 2 - 66th + 1080 (a) (a -) 2 - 66th + 1080 We need two numbers whose sum is 66 and product 1080. When we break 1080: 1080 5 40 270 135 45 15 5 1 105 + 8 = 113, do not serve 45 + 24 = 69, do not serve 30 + 36 = 66, it serves 2 2 2 3 3 3 5 2 × 2 × 2 = August 2 × 2 × 2 × 3 = 24 2 × 3 × 5 = 30 3 × 3 × 3 × 5 = 105 3 × 3 × 5 = 45 2 × 2 × 3 × 3 = 36 The numbers that we are 30 and 36, because their sum is 66 and its product neces sarily 1080, because we use these numbers for all the factors obtained in the de composition of 1080, thus: 2 - 66th + 1080 = (a - 36) (a - 30) Page 12 of 13 Decomposition of a polynomial into factors by the method of evaluation (Ruffini) Paolo Ruffini (1765-1822): How old are alive? Italian mathematician and physicia n, born in Rome. By studying the divisibility by x - to prove that if an integer and rational pol ynomial in x vanishes for x = a, the polynomial is divisible by x - a. The same principle applies to the decomposition of a polynomial into factors Evaluation M ethod. Examples 1) for assessment Decompose x 3 + 2x 2 - x - 2 x The values give are the factors of two independent terms: + 1, - 1, + 2 and - 2. Let's see if t he polynomial vanishes for x = 1, x = - 1, x = 2, x = - 2, and if it vanishes fo r some of these values, the polynomial is divisible by x less than that value. A pplying the division will be explained in advance if the polynomial vanishes for these values of x simultaneously find the coefficients of the quotient of the d ivision. In this case: +1 coefficients of the polynomial coefficients of the quo tient January 1

1 1 2

2 2 2 0

3 3

The residue is 0, meaning that the polynomial vanishes for x = 1, then is divisi ble by (x - 1). Divide x 3 + 2x 2 - x - 2 between x - 1, the quotient will be th e second degree and their coefficients are +1, +3 and +2, then the ratio is +1 x 2 +3 x +2 = x 2 +3 x + 2 and as the dividend is equal to the product of the div isor by the quotient, we have: x 3 + 2x 2 - x - 2 = (x - 1) (x 2 + 3x + 2) (fact oring the trinomial) = (x - 1) (x + 1) (x + 2) Page 13 of 13 2) Decompose by evaluating x 3 - 3x 2 - 4x + 12 12 factors are ± (1, 2, 3, 4, 6, 12) 1 1 1 3 1 2 4 2 6 +12 June 6 coefficients of the polynomial c oefficients of the quotient The residue is 6, then the polynomial does not vanish for x = 1,and is not divi sible by (x - 1) -1 1 1 1 3 4 4 +4 0 +12 0 +12 coefficients of the polyn omial coefficients of the quotient The residue is 12, then the polynomial does not vanish for x = - 1 and not divis ible by x - (- 1) = x + 1 1 3 +2 4 2 1 +12 6 12 0 Coefficients quoti ent of the polynomial coefficients 1 +2 The residue is 0, then the polynomial is zero 2) The quotient of dividing the polynomial x second degree and their coefficients are +1, x 2 - 1x - 6 = x 2 - x - 6. Therefore: x 3 - 6) (factoring the trinomial) = (x - 2) (x for x = 2 and is divisible by (x 3 - 3x 2 + 4x + 12 by x - 2 is the - 1 - 6, then the ratio will be +1 3x 2 + 4x + 12 = (x - 2) (x 2 - x 3) (x + 2)